Perancangan Media Pembelajaran Berbasis Augmented Reality dengan Metode Marker Based Tracking pada Mata Pelajaran Perakitan Komputer - Rahayu ‎, Emilia Gusti; Efriyanti, Liza (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated because learning is still important for teachers. Teachers have not usedaugmented reality-based learning media, especially smartphones, teachers still use powerpoint in learning, besides that students also have not been able to take full advantage of smartphone technology in the field of education. So the formulation of the problem in this research is how to design learning media based on augmented reality in the subject of Computer Assembly class X at SMKN 2 Guguak. And the purpose of this research is to design learning media based on Augmented Reality on the subjectof Computer Assembly Class X SMKN 2 Guguak. The method used in this research is R&D with theLuther-Sutopo version of the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept (conception), design (design), material collector (material collection). , assembly (manufacturing), testing (testing) and distribution (distribution). There are product tests carried out in this study, namely validity tests given to field experts or field experts, practicality tests carried out by computer assembly subject teachers and students and effectiveness tests given to two learning teachers and five students. students of SMKN 2 Guguak Class X.‎ Based on the product test results that the authors have tested for validity, the average value is 0.93 which is declared valid, and for the practicality test the average value is 0.97 which is declared practical and for effectiveness. test to get an average value of 0.83 which is declared effective.